Pengaruh Desain Produk, Brand Image, Dan Perilaku Konsumen Terhadap Keputusan Pembelian Vitamin Xon-Ce Di Apotek Jasmine - Novitri, Afridilla Novitri; Realize, Realize (SCIENTIA JOURNAL, 2023)
This study aims to analyze the influence of product design, brand image, and consumerbehavior on purchasing decisions of Vitamin Xon-Ce at Jasmine Pharmacy. This researchmethod uses descriptive research with a quantitative approach. The population of thisstudy are consumers who consume xon-ce vitamins in Batam City, where the exactamount is not known. The technique of determining the sample through the Jacob Cohenformula with the results of calculating as many as 240 respondents based on purposivesampling. The findings in the multiple linear regression analysis state that product designcan contribute an increase of 36.5% to purchasing decisions. Brand image can contributean increase of 20.0% to purchasing decisions. Consumer behavior can contribute anincrease of 47.9% to purchasing decisions. The results of the analysis of the coefficient ofdetermination (R2) state that product design, brand image and consumer behavior cancontribute 67.4% to purchasing decisions. The results of the t and F test show that productdesign, brand image, and consumer behavior have a positive and significant effect partiallyand simultaneously on purchasing decisions